New molecular markers for quantifying abundance and gene expression of widespread and often undetected marine N2 fixing symbionts of diatoms - Ström, Linnéa M. V.; Ley, Philip; Webb, Eric A.; Hutchins, David A.; Saito, Mak; Lundin, Daniel; Foster, Rachel A. (Frontiers in Protistology, 2025)
IntroductionDecades of research has been devoted to understanding the occurrence, distribution, and activity of different N2-fixers in the oceans. Marine N2-fixing diatom symbioses involving the heterocyst-forming cyanobacterium Richelia are widespread, yet often go undetected. Some of the diatom-Richelia symbioses have the advantage to be identified by microscopy, however, observations alone cannot inform on the metabolic state of a cell. MethodsHere, we developed nine new specific quantitative PCR assays that detect three common symbiotic Richelia strains (ReuHH01, RintRC01, RrhiSC01) of diatoms based on molecular markers for: a high affinity phosphate transporter (pstS), an iron transporter (exbB), and a constitutively expressed gene (rnpA, protein component of ribonuclease P). We first tested the new assays in the lab, including a diel experiment to elucidate the temporal dynamics of gene expression for each molecular marker, then applied the new assays to field collected samples. In the field we also made microscopy observations of the diatom-Richelia symbioses and measured bulk N2 and Carbon (C) fixation rates with stable isotope labelling incubations. ResultsThe number of genes encoding the molecular markers varied; typically, fewer in the endobiont strains. Detection in field samples based on qPCR was consistent with microscopy observations. The environmental gene expression for all the new targets, and additionally nifH for N2 fixation (nitrogenase) were low, and highest expression was detected in the upper water column (0-40 m) consistent with higher densities of the Richelia by qPCR and microscopy observations. Low in situ bulk rates of N2 and C fixation corroborated the aforementioned low nifH expression. Expression of both nifH and pstS was temporally regulated in the lab experiment of the facultative symbiotic Richelia strain RrhiSC01 with higher expression in the early and late photoperiods, respectively. DiscussionThe nine new assays are an improvement over the previous assays based on the nifH gene as cross-reactivity between Richelia strains is minimum, expression can be normalized to rnpA, and expression is informative of the symbiont nutrient status.